Detection of Pepino Mosaic Virus in Imported Tomato Fruit in Northern Europe - Just, Kadri; Arif, Usman; Kõrve, Elisabeth‐Lisette; Paats, Pille; Kvarnheden, Anders (Plant pathology, 2025)
ABSTRACT Infection with pepino mosaic virus (PepMV) was detected in imported tomato fruit on the market in northern Europe using lateral flow tests, reverse transcription (RT)‐PCR‐restriction fragment length polymorphism (RFLP) and sequence analysis of the coat protein (CP) gene. Traded tomatoes imported from Europe, Africa and the Middle East were collected in Estonia and Sweden. Out of 110 batches analysed with five fruits sampled in each batch (100 batches from Estonia and 10 from Sweden), 69 batches were positive (63 from Estonia and six from Sweden). Restriction endonuclease digestion of RT‐PCR products for 44 tomato batches revealed the presence of five PepMV strains (CH2, EU, LP, US2 and US1) either in single or mixed infections in different combinations. Most samples (24) had a single infection with the CH2 strain, three samples had a single infection with the US2 strain and one sample with the EU strain. Nine samples had a mixed infection with CH2 and US2 strains, while one sample had a mixed infection with EU and CH2 strains, one with LP and US2, and one with CH2 and US1 strains. In addition, four samples had a triple infection with CH2, EU and US2. Sequencing of the CP gene for 10 samples revealed 98% nucleotide identity to isolates of the CH2, EU and US2 strains. In this study, PepMV was identified for the first time in imported tomato fruit on the market in northern Europe, and the results indicate a wide distribution of PepMV with considerable genetic variability. PepMV was detected in imported tomatoes in northern Europe using rapid tests, RT‐PCR‐RFLP and sequencing, revealing diverse strains (CH2, EU, LP, US1 and US2) and mixed infections with broad distribution and genetic variability.